2013
DOI: 10.4314/ajtcam.v10i2.19
|View full text |Cite
|
Sign up to set email alerts
|

Herbal medicines used by Bapedi traditional healers to treat reproductive ailments in the Limpopo Province, South Africa

Abstract: The current study focussed on documenting the ethnobotanical knowledge of herbal medicines used by the Bapedi traditional healers to treat reproductive ailments in the Limpopo Province, South Africa. Fifty one healers from 17 municipalities covering Capricorn, Sekhukhune and Waterberg districts of the Limpopo Province were interviewed between January and July 2011. Semi-structured interviews, observations and guided field surveys with the healers were employed. Thirty-six medicinal plant species belonging to 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 39 publications
0
14
1
Order By: Relevance
“…Similar findings were also reported by Kamatenesi-Mugisha and Oryem-Origa ( 2007 ), who noted the extensive use of leaf remedies for inducing labor during childbirth in Western Uganda. The present survey is in conflict with the findings of Semenya et al ( 2013 ), who reported that roots and bark were the most commonly harvested plant parts used to treat reproductive ailments in the Limpopo province of South Africa. It was reported that collection of roots, bark, and whole plants might kill plants in harvest (Chinsembu and Hedimbi 2010 ; Kamatenesi et al 2011 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Similar findings were also reported by Kamatenesi-Mugisha and Oryem-Origa ( 2007 ), who noted the extensive use of leaf remedies for inducing labor during childbirth in Western Uganda. The present survey is in conflict with the findings of Semenya et al ( 2013 ), who reported that roots and bark were the most commonly harvested plant parts used to treat reproductive ailments in the Limpopo province of South Africa. It was reported that collection of roots, bark, and whole plants might kill plants in harvest (Chinsembu and Hedimbi 2010 ; Kamatenesi et al 2011 ).…”
Section: Discussioncontrasting
confidence: 99%
“…are used to treat eczema [ 36 , 37 ]. Roots or rhizome decoction of E. elephantina is taken orally as remedy for various ailments and diseases including anemia in Mozambique [ 25 ], blood pressure, clearing air canal, erectile dysfunction, haemorrhoids, itching, kidney failure, intestinal disorders, menstrual disorders, peptic ulcers, rheumatic conditions, shingles, sores, syphilis, and tonsillitis in South Africa [ 4 , 12 , 15 , 31 , 38 , 44 , 47 , 48 , 50 ]. In Botswana, rhizome or root powder of E. elephantina is used to wipe the anus of children with bloody diarrhoea, to clean the womb after abortion, as remedy for early menstruating children, earache, erectile dysfunction, and sexually transmitted infections [ 21 , 40 , 41 ].…”
Section: Ethnomedicinal Uses Of Elephantorrhiza Elephantmentioning
confidence: 99%
“…Root decoction taken orally (Gelfand et al, 1985) Female infertility and prevent miscarriage Bark and root decoction taken orally (Semenya et al, 2013); (Mhlongo and Wyk, 2019) Fever…”
Section: Dysmenorrhoeamentioning
confidence: 99%